Can Clinical Assessment of Postural Control Explain Locomotive Body Function, Mobility, Self-Care and Participation in Children with Cerebral Palsy? - Vlčkova, Blanka; Halámka, Jiří; Müller, Markus; Sanz-Mengibar, Jose Manuel; Šafářová, Marcela (Healthcare (Basel, Switzerland), 2024)
UNLABELLED: Trunk control may influence self-care, mobility, and participation, as well as how children living with cerebral palsy (CP) move around. Mobility and Gross Motor performance are described over environmental factors, while locomotion can be understood as the intrinsic ontogenetic automatic postural function of the central nervous system, and could be the underlying element explaining the relationship between these factors. Our goal is to study the correlation among Trunk Control Measurement Scale (TCMS) and Pediatric Evaluation of Disability Inventory (PEDI) domains, as well as Locomotor Stages (LS). METHODS: A feasibility observational analysis was designed including 25 children with CP who were assessed with these scales. RESULTS: The strong correlation confirms higher levels of trunk control in children with better self-care, mobility and participation capacities. Strong correlations indicate also that higher LS show better levels of PEDI and TCMS domains. CONCLUSIONS: Our results suggest that more mature LS require higher levels of trunk control, benefitting self-care, mobility and social functions.
Keywords: social participation; locomotor activity; postural balance; self-care; cerebral palsy